Chemical Communication in Artificial Cells: Basic Concepts, Design and Challenges - Karoui, Hedi; Patwal, Pankaj Singh; Pavan Kumar, B. V. V. S.; Martin, Nicolas (Frontiers in Molecular Biosciences, 2022)
In the past decade, the focus of bottom-up synthetic biology has shifted from the design of complex artificial cell architectures to the design of interactions between artificial cells mediated by physical and chemical cues. Engineering communication between artificial cells is crucial for the realization of coordinated dynamic behaviours in artificial cell populations, which would have implications for biotechnology, advanced colloidal materials and regenerative medicine. In this review, we focus our discussion on molecular communication between artificial cells. We cover basic concepts such as the importance of compartmentalization, the metabolic machinery driving signaling across cell boundaries and the different modes of communication used. The various studies in artificial cell signaling have been classified based on the distance between sender and receiver cells, just like in biology into autocrine, juxtacrine, paracrine and endocrine signaling. Emerging tools available for the design of dynamic and adaptive signaling are highlighted and some recent advances of signaling-enabled collective behaviours, such as quorum sensing, travelling pulses and predator-prey behaviour, are also discussed.